FREE RECALL: HAVE WE BEEN LOOKING AT THE WRONG CURVE? - Eugen Tarnow (Peoples' Friendship University of Russia (RUDN University), 2015)
I show that without the serial position curve, free recall can appear just as simple as integer recognition. The total search in word free recall, averaged over item position, increases linearly with the number of items recalled. Thus the word free recall search algorithm scales the same as the low-error recognition of integers [13]. The linear scaling of the search algorithm is different from what is commonly assumed to be the word free recall search algorithm, search by random sampling. The proportionality constant of 2-4 seconds per item (a hundred times larger than for integer recognition) is a power function of the average proportion not remembered and seems to be explicitly independent of subject age, presentation rate and whether there is a delay after the list presentation or not. The linearity of the word free recall extends down to 3 items which presents a challenge to the prevalent working memory theory in which 3-5 items are proposed to be stored in a separate high-availability store